2016
DOI: 10.1007/s00345-016-1903-6
|View full text |Cite
|
Sign up to set email alerts
|

Second-line treatment for metastatic clear cell renal cell cancer: experts’ consensus algorithms

Abstract: In contrast to the first-line setting, recommendations for second-line systemic treatment of mccRCC among experts were not as heterogeneous. The agents mostly used after disease progression on a first-line TKI included: EVE, AXI, NIV and sTKI. In the future setting of NIV and CAB availability, NIV was the most commonly chosen drug, whereas several experts identified situations where CAB would be preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Cytoreductive nephrectomy (CN) has been an integral part of a multimodal management concept of patients with synchronous metastatic renal cell carcinoma (mRCC) treated with cytokines, as two randomised controlled trials demonstrated a significant overall survival (OS) advantage before treatment with interferon-alphabased therapy [1][2][3]. Over the past decade, targeted therapies (TT) with VEGF receptor tyrosine kinase inhibitors (TKI) and mammalian target of rapamycin (mTOR) inhibitors have replaced cytokine treatment and are now the accepted standard of care [4,5]. Since the inception of these agents, both the role of upfront CN and the timing of CN have been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Cytoreductive nephrectomy (CN) has been an integral part of a multimodal management concept of patients with synchronous metastatic renal cell carcinoma (mRCC) treated with cytokines, as two randomised controlled trials demonstrated a significant overall survival (OS) advantage before treatment with interferon-alphabased therapy [1][2][3]. Over the past decade, targeted therapies (TT) with VEGF receptor tyrosine kinase inhibitors (TKI) and mammalian target of rapamycin (mTOR) inhibitors have replaced cytokine treatment and are now the accepted standard of care [4,5]. Since the inception of these agents, both the role of upfront CN and the timing of CN have been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Several first‐line treatment alternatives with targeted therapies exist, including the tyrosine kinase inhibitors (TKIs) sunitinib and pazopanib . However, patients often develop biological resistance and receive second‐line treatment . Axitinib is a potent and selective oral TKI targeting the VEGF receptors (VEGFR) 1, 2, and 3 and primarily displays antiangiogenic activity.…”
mentioning
confidence: 99%
“…Axitinib is a potent and selective oral TKI targeting the VEGF receptors (VEGFR) 1, 2, and 3 and primarily displays antiangiogenic activity. The drug is approved in Europe, the United States, Japan, and elsewhere for the treatment of advanced renal cell carcinoma (RCC) after failure of one prior systemic therapy, and is currently a preferred choice as second‐line therapy for patients progressing after first‐line therapy . Moreover, axitinib has shown clinical activity in first‐line mRCC in recent phase II and III trials .…”
mentioning
confidence: 99%
“…The participants were initially asked to answer the following open question: “What is your treatment policy regarding pre‐ and/or postoperative chemotherapy in localized extremity STS?” For the purposes of the present analysis, additional treatment such as isolated limb perfusion (ILP) and regional hyperthermia (RH) were not considered, even though they supplement surgery, radiotherapy, and chemotherapy in some of the centers. The initial answers provided were collected and converted into decision trees by the coordinating center (St. Gallen), based on the objective consensus methodology as published previously . This process consisted of an initial manual transformation of the replies into simple decision trees; once these were created, the respondents were contacted again to fill in possible empty branches of the decision trees.…”
Section: Methodsmentioning
confidence: 99%